2015
DOI: 10.1186/s40779-015-0062-1
|View full text |Cite
|
Sign up to set email alerts
|

Syncope as a health risk for soldiers - influence of medical history and clinical findings on the sensitivity of head-up tilt table testing

Abstract: BackgroundSyncope is a relevant health problem in military environments. Reliable diagnosis is challenging. Tilt table testing is an important tool for syncope diagnosis. The aim of this study was to determine whether signs such as prodromal symptoms, co-morbidity, frequency of syncopal events, body length, body mass index, and electrocardiography abnormalities can be used to predict the success of tilt table testing at diagnosing syncope.MethodsData from 100 patients with histories of syncope or pre-syncope, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Orthostatic responses were recently found by our study group to be influenced by age, gender, body weight status and the level of physical fitness . Regarding the impact of body weight status on OI, cross‐sectional studies investigating the relationship between orthostatic responses and body mass index (BMI) found conflicting results . Moreover, studies evaluating the effects of bariatric surgery have consistently reported increased OI and propensity to NCS after surgically induced weight loss, although these studies were only case reports or they had a small number of participants .…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Orthostatic responses were recently found by our study group to be influenced by age, gender, body weight status and the level of physical fitness . Regarding the impact of body weight status on OI, cross‐sectional studies investigating the relationship between orthostatic responses and body mass index (BMI) found conflicting results . Moreover, studies evaluating the effects of bariatric surgery have consistently reported increased OI and propensity to NCS after surgically induced weight loss, although these studies were only case reports or they had a small number of participants .…”
Section: Introductionmentioning
confidence: 83%
“…Regarding the first setting, an important consideration is the aggressiveness of the HUT protocol, as determined by the angle of tilt table, the duration of passive phase and whether or not pharmacological provocation was performed. Studies using too aggressive protocols failed to find a significant difference in BMI between individuals with positive and the ones with negative result during HUT, while studies using less aggressive protocols showed that BMI of the positive responders was lower compared with the one of the negative responders (Table 1) (3,4,7,18,19). A possible explanation for these findings is that the more aggressive the HUT protocol is, the higher the incidence of positive responses is in individuals with higher BMI values, diminishing any difference in the positive responses between individuals with different BMI values.…”
Section: Excess Body Weightmentioning
confidence: 99%
“…In a study of 178 subjects with recurrent syncope who underwent a head-up tilt test (HUTT), male gender (HR 0.61) and smoking (HR 0.18) were significantly protective for syncope following nitroglycerin provocation 14. Previous studies have shown that height is a predictive factor, in terms of a positive HUTT15 or time to syncope using supine lower body negative pressure (LBNP),16 although height does not appear to explain the gender difference in orthostatic tolerance 17. We found no significant difference in height (Table 3) in the syncope group, even when we specifically compared those with orthostatic-mediated reflex syncope (Table 1), and control group.…”
Section: Discussionmentioning
confidence: 99%
“…In Gilfrich et al [10] a study assessed the Syncope as a health risk for soldiers-influence of medical history and clinical findings on the sensitivity of head-up tilt table testing on 100 consecutive patients aiming to identify major and minor criteria that might suggest diagnostic benefit from head-up tilt testing included 55% female and45% male patients with mean age of population study 53 years.…”
Section: Discussionmentioning
confidence: 99%